The Young Milton: the individuation between church and social education - Geraldo Magela Pereira Leão; Paulo César Rodrigues Carrano (Universidade Federal do Rio Grande do Sul, 2013)
This article discusses the processes of transition to adulthood of contemporary youth based on a selected case from a study of the biographical trajectories of young participants in a social project. Theempirical corpus consisted of in-depth biographical interviews, longitudinal monitoring of daily activities, drawing maps of routes for young people and a group discussion. The analysis of the young Milton's trajectory shows his formulation of strategies to overcome existential situations. These strategies were possible through his process of learning that allowed him to constitute an individualized social capital, which propelled him beyond the objective conditions of his social context.